Evaluating the effect of barrel length on pellet distribution patterns of sawn-off shotguns. (March 2021) - Maitre, Matthieu; Chiaravalle, Analisa; Horder, Mark; Chadwick, Scott; Beavis, Alison
Highlights: The pellet areas from six shotguns were studied at several target distances. Shotguns were shortened to determine effect of barrel length on pellet area. The choke and distance from the target were found to have the greatest impact. The distinction of unaltered and altered shotguns was investigated using PCA. Abstract: In recent years, sawn-off shotguns have been regularly encountered in firearm-related incidents. Shotgun represents a community threat due to their ability to be shortened in order to improve their concealability. In practice, forensic scientists and investigators may be asked to determine if a shotgun used in a particular event might have been shortened based on the pellet distribution. To investigate the effect of altering the barrel length on pellet distribution, five 12-gauge shotguns were progressively shortened. Each shotgun was assessed at six barrel lengths and a single discharge of No. 4 shot shotshell ammunition was fired at a fixed fabric target. The shotguns were positioned at six different distances from target and experiments conducted in triplicate. The fabric targets containing pellet pattern underwent data analysis to calculate the pellet distribution area. At short distances from target (≤ 1.0 m), the pellet penetration was observed as a single entry point as the pellets did not have a sufficient flight time to spread from each other. For distances of 2.5 m, 5 m and 10 m, pellet penetration patterns were observed and a quantitative analysis was performed on the samples containing pellet distribution patterns. At each of these distances, it was detected that there was a noticeable increase in pellet distribution area between the unaltered shotgun and altered barrel lengths for all shotguns. The distance from the target as well as the presence of a choke in the shotgun's barrel was found to have a greater impact on the pellet distribution than the barrel length.